2015
DOI: 10.4103/2230-973x.153385
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of sustained release dosage form of moisture sensitive drug

Abstract: Objective:The purpose of this study was to prepare sustained release tablet of moisture sensitive drug like Ranitidine Hydrochloride for treatment of gastroesophageal reflux disease along with the improvement of moisture stability to get better therapeutic efficacy.Materials and Methods:Pan coating technique was used for coating of the tablet. Film coating was done using Eudragit RLPO and Eugragit EPO as coating polymer. 32 full factorial design was applied for optimization purpose, and 9 runs were conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Hardness [14] The resistance of tablets to shipping or breakage under condition of storage, transportation and handling before usage depends on its hardness. The hardness of each batch of tablet was checked by using Monsanto hardness tester.…”
Section: Evaluation Of Prepared Formulationsmentioning
confidence: 99%
“…Hardness [14] The resistance of tablets to shipping or breakage under condition of storage, transportation and handling before usage depends on its hardness. The hardness of each batch of tablet was checked by using Monsanto hardness tester.…”
Section: Evaluation Of Prepared Formulationsmentioning
confidence: 99%
“…An example is the combination of hydrophilic commercial polymers Eudragit ® E PO and Eudragit ® RLPO for the coating of moisture-sensitive ranitidine hydrochloride, a treatment for gastroesophageal reflux disease. The coated tablets displayed superior moisture protection over its marketed formulation RANTEC 300, where it gained only 10–15% moisture compared with 35–40% in RANTEC300 after 170 h in 75%RH, proving the effectiveness of hydrophilic polymer combinations as moisture-protective barriers [ 34 ].…”
Section: Formulation Strategies To Reduce or Control Hygroscopicitymentioning
confidence: 99%
“…Many efforts have been made to develop effective formulations and maintain product stability of ranitidine hydrochloride [ 82 ]. Patel et al [ 83 ] reported that film coating using a combination of Eudragit ® EPO and Eudragit ® RLPO was effective in improving moisture stability and enhancing therapeutic efficacy of ranitidine hydrochloride [ 83 ].…”
Section: Pharmaceutical Application Of Film Coatingmentioning
confidence: 99%